Peran Warna Desain Interior terhadap Perasaan Tenang Pengunjung SPA “Martha Tilaar”: The role of colors psychology in interior design towards Spa's Visitors : Study case of Martha Tilaar - Monica, Agnes; Darmayanti, Tessa Eka (Waca Cipta Ruang, 2022)
The interior design of the Spa room is currently of particular concern in improving its quality as a support for the psychological recovery of visitors in order to provide a comfortable and quiet room, one of which is the consideration of the color of the space. Color is a significant element of the interior since a layer of paint may dramatically modify the interior, disguise design problems can even change the psychological state of the individual who is in the room and if the person is tired, color can "disguise" it. The purpose of this study was to determine the role of color in the Spa room in the psychological effects felt by visitors. This study uses a qualitative method with literature studies and interviews related to the topic of discussion. The results of this study show that the use of a single color (monochrome) and a combination of contrasting colors give a different impression and impact on the individual's psychology and the atmosphere of the room. A monochrome can provide calm while contrasting colors give a passionate effect that is not properly implemented in spa facilities. In addition, it is hoped that this can also be used as a reference for designing spa rooms by considering the color of the space and its psychological effect on spa visitors. Keywords: Interior Design, Spa visitors, Color psychology